2010
DOI: 10.1017/s0043933910000504
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of corn distillers dried grains with solubles as an ingredient of poultry diets: A review

Abstract: A rapid increase in corn use in ethanol plants, and subsequent creation of distillers dried grains with solubles (DDGS) by-products, has led to an increase in the use of DDGS in the diets of livestock. DDGS has been used all over the world as a dietary ingredient and this has necessitated more research to be conducted on its quality, nutritive values, and recommendations for feeding to poultry. Currently, there have been a limited number of research publications regarding corn DDGS as an ingredient of diets fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 69 publications
(78 reference statements)
8
34
2
2
Order By: Relevance
“…Thus, the average values of calcium, phosphorus, copper, iron, manganese and zinc in RDP of present study are increased between 2 and 9 times in comparison with value of brown rice. The results of this study are in agreement with previous studies [4,5,6,21] who indicated that most mineral contents of DDGS are at least 3 times higher than those of the grain from which it originated. In the present study, average phosphorus content in the rice distiller's by-product samples analysed was within the range of published values in DDGS of previous reports [4,5,6,19,20,21].…”
Section: Nutritional Value Of Rice Distiller's By-productssupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, the average values of calcium, phosphorus, copper, iron, manganese and zinc in RDP of present study are increased between 2 and 9 times in comparison with value of brown rice. The results of this study are in agreement with previous studies [4,5,6,21] who indicated that most mineral contents of DDGS are at least 3 times higher than those of the grain from which it originated. In the present study, average phosphorus content in the rice distiller's by-product samples analysed was within the range of published values in DDGS of previous reports [4,5,6,19,20,21].…”
Section: Nutritional Value Of Rice Distiller's By-productssupporting
confidence: 93%
“…The results of this study are in agreement with previous studies [4,5,6,21] who indicated that most mineral contents of DDGS are at least 3 times higher than those of the grain from which it originated. In the present study, average phosphorus content in the rice distiller's by-product samples analysed was within the range of published values in DDGS of previous reports [4,5,6,19,20,21]. Calcium level in RDP was lower than in DDGS as reported by previous studies [19,20] or slightly higher [4,5].…”
Section: Nutritional Value Of Rice Distiller's By-productssupporting
confidence: 93%
See 3 more Smart Citations